2016
DOI: 10.1128/aem.02199-16
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas brassicacearum Strain DF41 Kills Caenorhabditis elegans through Biofilm-Dependent and Biofilm-Independent Mechanisms

Abstract: Pseudomonas brassicacearum DF41 is a biocontrol agent that suppresses disease caused by the fungal pathogen Sclerotinia sclerotiorum. A number of exometabolites are produced by DF41, including the lipopeptide sclerosin, hydrogen cyanide (HCN), and degradative enzymes. The production of these compounds is controlled at both the transcriptional and posttranscriptional levels by quorum sensing (QS) and the Gac two-component regulatory system. In order to be successful, a biocontrol agent must persist in the envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Therefore it is not surprising that bacteria have evolved defensive mechanisms to resist predation. A study investigating the interaction of DF41 and the model organism Caenorhabditis elegans revealed that DF41 was capable of killing the nematodes through two distinct mechanisms [25]. The first involved exposure to toxic bacterial metabolites, in particular HCN, which induced nematode death [25].…”
Section: Alternative Functions For Antibiotics/secondary Metabolites mentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore it is not surprising that bacteria have evolved defensive mechanisms to resist predation. A study investigating the interaction of DF41 and the model organism Caenorhabditis elegans revealed that DF41 was capable of killing the nematodes through two distinct mechanisms [25]. The first involved exposure to toxic bacterial metabolites, in particular HCN, which induced nematode death [25].…”
Section: Alternative Functions For Antibiotics/secondary Metabolites mentioning
confidence: 99%
“…A study investigating the interaction of DF41 and the model organism Caenorhabditis elegans revealed that DF41 was capable of killing the nematodes through two distinct mechanisms [25]. The first involved exposure to toxic bacterial metabolites, in particular HCN, which induced nematode death [25]. HCN is known to cause lethal paralysis by inhibiting mitochondrial cytochrome oxidase in C. elegans [71,128].…”
Section: Alternative Functions For Antibiotics/secondary Metabolites mentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have raised the possibility that bacterial biofilm formation is important in the process of biocontrol (Al-Ali et al, 2017;Chen et al, 2013). Indeed, the formation of a biofilm in the buccal cavity of the nematode, Caenorhabditis elegans, has been cited as an active virulence factor for the biocidal effect of Pseudomonas brassicacearum (Nandi et al, 2016). This process could be relevant to the use of the bacterium as a biocontrol agent for nematodes.…”
Section: Probiotic Trait: the Significance Of Biofilm Formation By Thmentioning
confidence: 99%